ANALYSIS COMMUNITY POTENTIALS FOR STRATEGY IMPLEMENTATION TO ENHANCE THE ABILITY OF CHIANG MAI COMMUNITIES IN ASEAN COMMUNITY - ทองบุญนาค กาญจนา; มินแสน ปรารถนา (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2018)
The objectives of this research were to study and compare the analysis community potentials for strategy implementation to enhance the ability of Chiang Mai communities in ASEAN community. The sample was the 21 agents from the local administrative organization from 7 communities in Chiang Mai who are willing to participate this seminar. This research was Participatory Action Research: PAR and analysis community potentials by SWOT. The research instruments were the form analysis community potentials for strategy implementation to enhance the ability of Chiang Mai communities in ASEAN community was collected two phrases; pre-test and post-test for 13 topics. The statistics for analyzing the data were mean, standard deviation and Wilcoxon Matched Pairs Signed Rank test. The results indicated that the posttest scores for the understanding of analysis Community Potentials for Strategy Implementation to were higher than the pre-test scores, statistically significant difference at .05 level.In addition, all the local administrative organization has maximized increase average score is the understanding of the ASEAN community strategic plan. Conversely, the community empowerment analysis of the elderly and the disabled in the community for implementation of the potential project is minimal increase.